Matrizes poliméricas de acetato butirato de celulose como suporte para sistemas luminescente a base de complexo de európio - Silva, Guilherme de Freitas (2023)
In this work, the polymer cellulose acetate butyrate (CAB) was doped with the luminescent complex Eu[TTA]3 from solutions combining three concentrations of polymers and three concentrations of complex. Its luminescent properties as a function of temperature were evaluated and discussed. The analysis and luminescence indicated that the synthesized material favored the internal transition of the europium ion, 5D0 → 7F2, mainly responsible for the complex's red-light emission, by providing a highly asymmetric and polarizable chemical environment around the europium ion, the matrix also contributed for the quantum efficiency of luminescence by reducing the rate of excited state deactivation by non-radiative pathways. The emission quantum efficiency in the composite reached a value of 38%, a significant increase when compared with the efficiency of the complex in the form of crystals (27%). The luminescence lifetime of the luminescent polymer decreased linearly with increasing temperature while the luminescence intensity showed an exponential reduction with increasing temperature, both properties proved to be suitable for use in temperature measurements. The variation in the concentration of the components during the synthesis did not significantly alter the result profiles of the obtained luminescent polymers.